Continuing care in community of older adults with chronic illness, following the service healthcare standard of WHO framework - Rungrojwattana, Wassana; Artsanthia, Jintana (Journal of health and health management, 2021)
This survey research aimed to study the situation of the continuity and coordination of cares in community of chronic illness by using WHO Framework which was based on healthcare services. Samples were the older adults with chronic illness in urban area. Fifty-three cases were collected. Questionnaires were tested by content validity and reliability with 3 experts with IOC of 0.98 and Cronbach’s alpha coefficient of 0.96. Descriptive analysis was analysed in percentage, mean and standard deviation. The results found that the perception of the continuing care framework of WHO 2018 of the opinion of patients, relationship and trust among providers were good at 4.03 out of 5. The longitudinal continuity in over view had the level of perception at 3.90. The informational continuity was fair at, 3.95. The integrated people-centered health services were good, at 4.07. The satisfaction with health care was good, at 4.21. Thus, continuing care in community of the older adults with chronic illness following WHO framework will be the background information for healthcare providers to develop the continuing cares which follow the standard of World Health Organization.